Russia resurrected : its power and purpose in a new global order - Stoner, Kathryn, 1965- (New York : Oxford University Press, 2021)
"This book refutes the idea that Russia plays a weak hand well in international politics. The book argues instead that Russia under Vladimir Putin's regime may not be as weak as is sometimes thought in the West. It takes a multi-dimensional approach in assessing Russian state power in international relations, going beyond metrics of power like relative strength of the economy, human capital, and size of the military, to also include the policy weight or importance of Russian firms and industries, as well as where geographically, Russian influence has spread globally. The book includes fresh empirical data on the Russian economy, demography and human capital, and conventional military and nuclear weaponry capacities in Russia relative to other great powers like China and the United States. The book argues that realpolitik alone does not explain Russian foreign policy choices under Putin. Rather, Putin's patronal autocratic regime and the need for social stability plays an important role in understanding when and why Russian power is projected in the 21st century"--
Is Russia resurrected? -- Russia as a regional power -- Where (else) in the world is Russia? -- The unsteady economic means of Russian power -- Russian society as power resource or constraint? -- Russian hard power: conventional and nuclear assets -- Russia's soft and sharp power - old wine in new bottles? -- The domestic determinants of Russia's resurrection.
Includes bibliographical references and index.
(3ebQQGJ OQGSjI dWdGH GdLGeYI (B2024.s
Keywords: Putin, Vladimir Vladimirovich, -- 1952- -- Influence; International relations -- Forecasting; Russia (Federation) -- Foreign relations -- 21st century; Russia (Federation) -- Politics and government -- 1991-; Russia (Federation) -- Economic conditions -- 1991-; Russia (Federation) -- Forecasting